Investigation of Antibacterial Activities of Indian Costus Root Extracts against Human Pathogenic Bacteria - Aween, Mohamed Mustafa; Ali Khayyal, Wijdan Salim; Alghazal, Mohamed Ali (Semarak Current Biomedical Technology Research Journal, 2025)
Indian costus is traditionally famous due to its potential therapeutic activities. The study aimed to examine the antibacterial activities of Indian costus root samples obtained from different countries. The roots were extracted using ethanol and water, and phytochemical screening showed the presence of various compounds. The antibacterial activities of the extracts were tested against clinical bacterial isolates (Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli and Klebsiella pneumonia), using different methods. The results demonstrated varying inhibition percentages on different bacterial strains when exposed to the extracts using microtiter plate assay. While the disc diffusion method showed negative results, the agar well diffusion method revealed positive results for hot ethanolic extracts against Streptococcus pyogenes and Klebsiella pneumonia. Additional testing of the most sensitive bacteria to Soxhlet extract showed inhibitory effects at lower concentrations (6.25mg/ml).